2022
DOI: 10.3390/s23010308
|View full text |Cite
|
Sign up to set email alerts
|

Low Complexity Radar Gesture Recognition Using Synthetic Training Data

Abstract: Developments in radio detection and ranging (radar) technology have made hand gesture recognition feasible. In heat map-based gesture recognition, feature images have a large size and require complex neural networks to extract information. Machine learning methods typically require large amounts of data and collecting hand gestures with radar is time- and energy-consuming. Therefore, a low computational complexity algorithm for hand gesture recognition based on a frequency-modulated continuous-wave (FMCW) rada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…There are several existing radar-based gesture recognition algorithms. They are based on different hardware architectures, including the continuous wave (CW) radar [10][11][12], the frequency-modulated continuous wave (FMCW) radar [7,8,[13][14][15][16][17][18][19][20], and the multipleinput multiple-output (MIMO) radar [8,21,22]. The CW radar is simple to design and has excellent Doppler sensitivity, but it lacks the resolution of range.…”
Section: Preliminary Workmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several existing radar-based gesture recognition algorithms. They are based on different hardware architectures, including the continuous wave (CW) radar [10][11][12], the frequency-modulated continuous wave (FMCW) radar [7,8,[13][14][15][16][17][18][19][20], and the multipleinput multiple-output (MIMO) radar [8,21,22]. The CW radar is simple to design and has excellent Doppler sensitivity, but it lacks the resolution of range.…”
Section: Preliminary Workmentioning
confidence: 99%
“…They used the NN as the feature extractor. Zhao et al [16] proposed a gesture detection system using the FMCW radar. They implemented Blender 4.0 to generate different hand gestures and trajectories.…”
Section: Preliminary Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the analysis of feature fusion methods in Section 4.2, due to the different experimental conditions of classification algorithms, we cannot judge the advantages and disadvantages of different classification methods by directly comparing the results of different studies, but we can find the common values or rules from the statistics. The widely used machine learning methods in gesture recognition are support vector machine (SVM) [27,73], K-nearest neighbor method (KNN) [66], and hidden Markov model (HMM) [74]. These methods are easy to implement but lack robustness and computational efficiency.…”
Section: Classification Algorithmsmentioning
confidence: 99%
“…Additional studies have enhanced the DTW algorithm for gesture recognition by adding path constraints and refining the matching procedure for gesture recognition [81]. According to the data in statistics [27,44,66,73,75], it can be found that machine learning algorithms are more suitable for problems with simple gestures, small sample categories, and quantity in gesture recognition, and deep learning algorithms tend to have better performance in gesture recognition problems with complex gestures and a larger number of samples.…”
Section: Classification Algorithmsmentioning
confidence: 99%